Novel phthalocyanines bearing 7-oxy-3-(3,5-difluorophenyl)coumarin moieties: Synthesis, characterization, photophysical and photochemical properties - (:unkn) unknown (ELSEVIER SCIENCE SA, 2015)
Two novel phthalonitriles,7-(2,3-dicyanophenoxy)-3-(3,5-difluorophenyl) coumarin (2), 7-(3,4-dicyanophenoxy)-3-(3,5-difluorophenyl) coumarin (3), and corresponding zinc(II)-, indium(III) phthalocyanines were prepared. Additionally, photophysical (fluorescence quantum yields and lifetimes), photochemical (singlet oxygen generation and photodegradation under light irradiation) and spectral properties of the resulting peripherally/non-peripherally tetra 7-oxy-3-(3,5-difluorophenyl) coumarin substituted zinc (II) and indium (III) phthalocyanines (4-7) were investigated. All compounds (1-7) were characterized by elemental analysis, IR, H-1 NMR, mass and UV-vis spectral data. The obtained 7-oxy-3-(3,5-difluorophenyl) coumarin bearing pure zinc (II) and indium (III) phthalocyanine complexes were well soluble in organic solvents and displayed good singlet-oxygen generation and appropriate photodegradation. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Coumarin; Zinc; Indium; Photodegradation; Singlet oxygen; PHOTODYNAMIC THERAPY; ZINC(II) PHTHALOCYANINE; INDIUM PHTHALOCYANINES; SUBSTITUTED GALLIUM; OPTICAL-PROPERTIES; COUMARIN; PHOTOSENSITIZERS; DERIVATIVES